Humanitarian Experience in Cameroon - Flores Jiménez, Iris; Boccalatte, Luis A. (Revista del Hospital Italiano de Buenos Aires, 2023)
This article reports on the humanitarian work carried out in the Batcham-Fiela Municipality, in the western region of Cameroon. A small surgical mission and training workshops for the population on hand washing and post-surgical wound care were carried out.